Encyclopedia of Drug Metabolism and Interactions 2012
DOI: 10.1002/9780470921920.edm086
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Modulators of Human Drug Metabolism: Drug Interactions with Fruits, Vegetables, and Botanical Dietary Supplements

Abstract: Plant secondary metabolites (PSMs) have been components of man's diet for millennia and are believed to have played a significant role in steering the functional development of xenobiotic metabolizing enzymes (XMEs) and transporters within the human gastrointestinal tract. Only recently, however, PSMs have been recognized as modulators of human drug disposition. Despite exposure to thousands of structurally diverse dietary phytochemicals, only a few appear to significantly modulate human drug‐metabolizing enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 545 publications
0
1
0
Order By: Relevance
“…Recently, studies assessing the effectiveness and safety of natural products as food/supplements and medical agents showed that their concomitant use sometimes caused serious undesirable effects on human health [ 22 , 23 , 24 , 25 , 26 , 27 ]. Furthermore, pharmacokinetic studies are also important to evaluate biological activities of the constituents of natural products because the active constituents must be fully absorbed and sufficiently distributed to the target organs or tissues for their pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies assessing the effectiveness and safety of natural products as food/supplements and medical agents showed that their concomitant use sometimes caused serious undesirable effects on human health [ 22 , 23 , 24 , 25 , 26 , 27 ]. Furthermore, pharmacokinetic studies are also important to evaluate biological activities of the constituents of natural products because the active constituents must be fully absorbed and sufficiently distributed to the target organs or tissues for their pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%